Ganglioside GM3 Has an Essential Role in the Pathogenesis and Progression of Rheumatoid Arthritis - Tsukuda, Yukinori; Iwasaki, Norimasa; Seito, Naoki; Kanayama, Masashi; Fujitani, Naoki; Shinohara, Yasuro; Kasahara, Yasuhiko; Onodera, Tomohiro; Suzuki, Koji; Asano, Tsuyoshi; Minami, Akio; Yamashita, Tadashi (PLOS ONE, 2012)
Rheumatoid arthritis (RA), a chronic systemic inflammatory disorder that principally attacks synovial joints, afflicts over 2 million people in the United States. Interleukin (IL)-17 is considered to be a master cytokine in chronic, destructive arthritis. Levels of the ganglioside GM3, one of the most primitive glycosphingolipids containing a sialic acid in the structure, are remarkably decreased in the synovium of patients with RA. Based on the increased cytokine secretions observed in in vitro experiments, GM3 might have an immunologic role. Here, to clarify the association between RA and GM3, we established a collagen-induced arthritis mouse model using the null mutation of the ganglioside GM3 synthase gene. GM3 deficiency exacerbated inflammatory arthritis in the mouse model of RA. In addition, disrupting GM3 induced T cell activation in vivo and promoted overproduction of the cytokines involved in RA. In contrast, the amount of the GM3 synthase gene transcript in the synovium was higher in patients with RA than in those with osteoarthritis. These findings indicate a crucial role for GM3 in the pathogenesis and progression of RA. Control of glycosphingolipids such as GM3 might therefore provide a novel therapeutic strategy for RA.